Advances in Accounting Behavioral Research - Karim, Khondkar E. (Advances in Accounting Behavioral Research Ser., 2021)
Advances in Accounting Behavioral Researchpromotes research across all areas of accounting, incorporating theory from, and contributing knowledge to, the fields of applied psychology, sociology, management science, ethics and economics.